Comparative Evaluation between the Efficacy of Preload Versus Coload to Avoid Spinal Induced Hypotension in Patients Undergoing Emergency Caesarean Section (Medical Forum Monthly, 2022)
Objective: To compare effectiveness of coload over preload in terms of frequency of spinal induce hypotension in patients undergoing emergency caesarean section.Study Design: Randomized controlled trial studyPlace and Duration of Study: This study was conducted at the Department of Anesthesiology, Pakistan Institute of Medical Sciences Islamabad from 30th November 2018 to 29th May 2019.Materials and Methods: Two hundred women undergoing emergency caesarean section, 18-40 years of age were included. Extreme fetal distress, dying emergency, eclamptic patients, patients with coagulopathy, spine surgery or deformity, increased risk of bleeding and serious cardiac issues were excluded. Group A women were given preload of 10ml/kg within 20 min prior to subarachnoid block while Group B were given coload of 10ml/kg was given just after the subarachnoid block. After giving spinal anesthesia to the patient, mean arterial blood pressure was monitored and hypotension was recorded at 1 minute, 3 minutes, 5 minutes, 8 minutes and 10 minutes.Results: The mean age of patients in group A was 26.27±6.38 years and in group B was 27.09±6.41 years. Majority of the patients 135 (67.50%) were between 18 to 30 years of age. The spinal induced hypotension in Group A (preload) was seen in 77(77.0%) while in Group B (coload) was seen in 46 (46.0%) patients (p=0.0001).Conclusion: Spinal induced hypotension can be reduced with coload as compared to preload in patients undergoing emergency caesarean section.